IMPLEMENTING THE COOPERATIVE GALLERY WALK MODEL IN SCIENCE INSTRUCTION: A STUDY ON THE HUMAN RESPIRATORY SYSTEM MATERIALS - Dewi, Cut Ratna; Ariangga, Ruli; Eriawati, Eriawati; Zahara, Nurlia; Fajriana, Nurul (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2025)
Effective learning should promote active student participation and foster a conducive classroom environment. However, preliminary observations revealed that science instruction, particularly on the topic of the Human Respiratory System, remained dominated by discussion methods and task assignments at the end of the lesson. To address this issue, a more interactive learning model is required—one that enhances student engagement—such as the Cooperative Gallery Walk model. This study aims to analyze the implementation of the Cooperative Gallery Walk model in science learning at Islamic junior high schools (MTs) and its impact on students’ learning outcomes. A descriptive quantitative method was employed, utilizing pre-test and post-test instruments for data collection. The data were analyzed using the N-gain formula to determine improvements in students’ understanding of the human respiratory system. The results showed a significant increase in students’ average test scores from 25.55 (pre-test) to 89.44 (post-test). The N-gain score of 0.842 (high category) indicates that the Cooperative Gallery Walk model is highly effective in enhancing students’ conceptual understanding. Thus, the implementation of this model has a positive effect on improving student learning outcomes in science education, especially in the subject matter of the human respiratory system.